Excision repair of nitrogen mustard-DNA adducts in Saccharomyces cerevisiae. - McHugh, P J (1999)
The bifunctional alkylating anticancer drug nitrogen mustard forms a variety of DNA lesions, including monoadducts and intrastrand and interstrand crosslinks. Although it is known that nucleotide excision repair (NER) is important in processing these adducts, the role of the other principal excision repair pathway, base excision repair (BER) is less well defined. Using isogenic Saccharomyces cerevisiae strains disrupted for a variety of NER and BER genes we have examined the relative importance of the two pathways in the repair of nitrogen mustard adducts. As expected, NER defective cells (rad4 and rad14 strains) are extremely sensitive to the drug. One of the BER mutants, a 3-methyladenine glycosylase defective (mag1) strain also shows significant hypersensitivity. Using a rad4/mag1 double mutant it is shown that the two excision repair pathways are epistatic to each other for nitrogen mustard sensitivity. Furthermore, both rad14 and mag1 disruptants show elevated levels of nitrogen mustard-induced forward mutation. Measurements of repair rates of nitrogen mustard N-alkylpurine adducts in the highly transcribed RPB2 gene demonstrate defects in the processing of mono-adducts in rad4, rad14 and mag1 strains. However, there are differences in the kinetics of adduct removal in the NER mutants compared to the mag1 strain. In the mag1 strain significant repair occurs within 1 h with evidence of enhanced repair on the transcribed strand. Adducts however accumulate at later times in this strain. In contrast, in the NER mutants repair is only evident at times greater than 1 h. In a mag1/rad4 double mutant damage accumulates with no evidence of repair. Comparison of the rates of repair in this gene with those in a different genomic region indicate that the contributions of NER and BER to the repair of nitrogen mustard adducts may not be the same genome wide.